Confinement of nanostructured CeO2 inside carbon nanotubes - Agasti, Nityananda (2018)
This study reveals confinement of nanostructured CeO2 inside graphitised carbon nanofibers (CeO2@GNF). A standard procedure has been developed for encapsulation of CeO2 nanoparticles inside GNF. In situ preparation of CeO2 encapsulated inside GNF, has been carried out by using gas phase thermal decomposition method and ionic liquid mediated method. CeO2@GNF composites have been characterized by TGA, Raman, XRD, HRTEM, STEM and EDX techniques. Precursor loading was found to influence, particle size, location of CeO2, thermal stability and catalytic activity of CeO2@GNF composite. Besides being hollow nanocontainer, GNF acts as a template for the growth of very small CeO2 nanoparticles of size 3nm with high degree of crystallinity and dispersity. Catalytic properties of nanostructured CeO2 confined inside GNF has been assessed in oxidation of cyclohexene. High conversion of the reactant, selective oxidation of allylic carbon centre and formation of selective oxidation product 2-cyclohexenenone are some of the notable features, attributed to the effect of spatial confinement of CeO2 inside GNF. To study metal-support interaction in a confined space, Pt/CeO2 encapsulated in GNF(Pt/CeO2@GNF) has been prepared. Addition of Pt into CeO2@GNF led to growth of Pt nanoparticles on step edges of CeO2 nanoparticles at CeO2-GNF interface.